Risk factors of violent death in rural Bangladesh, 1990-1999 - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2020)
The study attempts to improve our understanding about the prevalence and determinants of violent death in rural Bangladesh. Data came from the demographic and health surveillance system of BRAC covering a population of nearly 62,000 in 70 villages in J 0 districts of the country. A standard verbal autopsy procedure was used to identify the causes of death. All non-disease specific deaths due to homicide, accident, drowning and suicide were considered violent death in this study. Findings reveal that the violent death rate was 28.3 per 100,000 persons per year during the 1990-1999. Drowning and homicide were the leading causes of death followed by the traffic accident and suicide. Significant sociodemographic differentials in violent death existed. The death rate was much higher among the «10 year old) children than the young adults and the old «0.01). Men were significantly more likely to die than women from aberrant causes. The violent death was higher among the poor than the rich, illiterates than the educated and among the Muslims than non-Muslims. When all predictors were considered together, the probability to become the victim of violent death was 61.2 per 100,000 if the person was very young, male, poor, illiterate and Muslim. The paper concludes that the public health program should consider the appropriate mechanisms to prevent many avoidable events of death in rural Bangladesh.